2021
DOI: 10.1590/s1678-9946202163039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic characterization of Dientamoeba fragilis in asymptomatic children attending daycare centers

Abstract: In order to provide additional data on the prevalence and genetic diversity of Dientamoeba fragilis in human populations, we conducted a study in children from low-income communities in Sao Paulo State, Brazil. Fecal samples from daycare center attendees up to 6 years old (n=156) and staff members (n=18) were submitted to PCR and sequencing of D. fragilis as well as to microscopic examination for the presence of other intestinal parasites. All children assessed wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…However, the conclusions of these studies are sometimes questionable since they are based on indirect results with no proven causal links. In addition, numerous studies have shown D. fragilis carriage without any clinical signs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the conclusions of these studies are sometimes questionable since they are based on indirect results with no proven causal links. In addition, numerous studies have shown D. fragilis carriage without any clinical signs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…fragilis detection by several stain methods is challenging and little is known about its impact in low- and middle-income countries. Studies in Latin America have shown prevalences up to 40% depending on the region and population group [ 66 ]. For instance, D .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, D . fragilis has been found in 15% of asymptomatic individuals [ 55 ] and 10.3% in children from Brazil [ 66 ] and 40.4% in a rural community in Venezuela [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations